Bibliometric mapping of the landscape and structure of nutrition and depression research: visualization analysis - Sa’ed H. Zyoud; Muna Shakhshir; Amani S. Abushanab; Amer Koni; Moyad Shahwan; Ammar A. Jairoun; Samah W. Al-Jabi (Journal of Health, Population and Nutrition, 2023)
Abstract Background Numerous epidemiological studies have examined the relationship between dietary intake of specific foods or nutrients and the incidence of depression and have noted that nutrition has a significant impact on mental health. Therefore, the purpose of this study is to assess the state of research, the frontiers of research, and development trends in the field of nutrition and depression using bibliometric and visual analysis. Methods We collected publications on the topic of nutrition and depression from Scopus between 2002 and 2021. Subsequently, we utilized VOSviewer 1.6.18 and Microsoft Excel 2013 to perform bibliometric analysis and visualization. Bibliometric analysis involves retrieving documents from a singular database, such as SciVerse Scopus or Web of Knowledge, and subjecting them to quantitative and qualitative analysis. Notably, gray literature is not considered in bibliometric analysis. Results A total of 2171 publications on nutrition and depression were found between 2002 and 2021, namely 1855 (85.44%) original articles, 190 (8.75%) reviews, 38 (1.75%) letters, and 88 (4.05%) other types of publications. The most productive country was found to be the USA (n = 726; 33.44%), followed by Australia (n = 172; 7.92%), the United Kingdom (n = 158; 7.28%), China (n = 132; 6.08%), and Canada (n = 131; 6.03%). The remaining publications were from other countries (n = 852; 39.25%). According to the citation analysis, the retrieved papers were cited on an average of 26.6 times and had an h-index of 105 with 57,781 citations. The most frequent terms on the map include those related to (a) fatty acid links to depression and brain inflammation, (b) depression and eating disorders, and finally, (c) adherence to the Mediterranean diet and risk of depression. Conclusions The current study was the first novel bibliometric analysis of nutrition and depression research that used data extracted from Scopus for visualization network mapping. In recent years, the theme "Mediterranean diet adherence and risk of depression" has been identified more frequently, indicating that studies in this field have garnered considerable attention and reflect the most recent scientific advances. Researchers should continue to investigate nutrition and depression, and we believe this study provides significant information for researchers, nutritionists, and clinicians.